PUSAT PERTANIAN DI SUNTER, JAKARTA UTARA - Maria Maureen; Sutrisnowati Machdijar Odang (Jurusan Arsitektur dan Perencanaan, 2022)
With a fixed amount of land and an increasing number of people, the government needs more residential land, by shifting the function of green land to be industrialized, especially in urban areas. This had such an impact on the farmers that the majority of the urban farmers retreated and went out of business. With the study of the Urban Acupuncture literature crossed with the decline in urban agriculture, this project intends to stimulate agricultural areas affected by the shift in land use above by using a system from the community for the community to revive the soul and surrounding habits that are starting to fade, namely agriculture, especially in the Sunter area, Jakarta Utara. With the location of the building which coincides with the JIS (Jakarta International Stadium) this project is intended to be a stimulus for the agricultural sphere as well as recreation to complement the JIS in the Sunter area. With the results as an outline of agriculture x Recreation, this project contains vertical agricultural land with various systems that support seeds, planting to sales management and also recreation which contains canteens, bazaars and communal areas to distribute more agricultural knowledge, bring people closer together and become a complementary recreation area for JIS itself. By becoming a link between the degradation of conventional urban agriculture with modern agriculture, it is hoped that in the future, this Agricultural Center project can be a driving force for the urban agricultural system to better adapt to the times. Keywords: Urban Acupuncture; Shifting Agricultural Land; Agricultural Center; Sunter Abstrak Dengan jumlah lahan yang tetap dan jumlah manusia yang kian bertambah, pemerintah membutuhkan lebih banyak lahan perumahan, dengan menggeser fungsi lahan hijau untuk diindustrialisasikan khususnya di perkotaan. Hal ini sangat berdampak bagi para petani sehingga mayoritas petani kota mundur dan menggulung tikar. Dengan kajian literatur Urban Acupuncture yang disilangkan dengan menurunnya pertanian perkotaan, proyek ini bermaksud menstimulasi kawasan pertanian yang terdampak pergeseran fungsi lahan diatas dengan menggunakan sistem dari masyarakat untuk masyarakat untuk menghidupi kembali jiwa serta kebiasaan sekitar yang mulai memudar yakni pertanian khususnya di daerah Sunter Jakarta Utara. Dengan lokasi bangunan yang bertepatan dengan JIS (Jakarta International Stadion) proyek ini dimaksudkan untuk menjadi stimulain bagi lingkup pertanian serta menjadi rekreasi untuk melengkapi adanya JIS di kawasan Sunter ini. Dengan hasil sebagai garis besar pertanian x Rekreasi, proyek ini berisikan lahan pertanian vertikal dengan berbagai sitem yang menunjang bibit, tanam hingga management penjualan dan juga rekreasi yang dimana berisikan kantin, bazar dan area komunal guna mendistribusikan lebih lagi pengetahuan pertanian, mendekatkan masyarakat antar masyarakat dan menjadi area rekreasi pelengkap JIS ini sendiri. Dengan menjadi penyambung antara degradasi pertanian perkotaan konvensional dengan pertanian modern, diharapkan kedepannya, proyek Pusat Pertanian ini dapat menjadi pendorong sistem pertanian perkotaan untuk lebih beradaptasi dengan perkembangan zaman.